2019
DOI: 10.12659/msm.915790
|View full text |Cite
|
Sign up to set email alerts
|

Atorvastatin Induces Hepatotoxicity in Diabetic Rats via Oxidative Stress, Inflammation, and Anti-Apoptotic Pathway

Abstract: BackgroundPatients with diabetes mellitus (DM) commonly receive statins to suppress vulnerability to adverse cardiovascular events. It has been clinically proven that hepatotoxicity is one of the most severe adverse effects of statins.Material/MethodsWe constructed diabetic rat models by feeding rats with high-fat food and by injection of low-dose STZ. Rats were randomized into 2 groups: a DM group (n=10) and a control (CON) group (n=5). CON rats received a normal diet, whereas DM rats ate high-fat food. Rats … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 36 publications
(32 reference statements)
0
12
0
Order By: Relevance
“…The transcriptome of pancreatic islets from mice with similar Ator treatment has also shown activated NF-κB signaling and enhanced metabolic inflammation (Shen et al, 2020). Though the anti-inflammatory effects of statins have been reported in traumatic brain injury, HFD-induced renal injury, endothelial dysfunction, and cardiac and adipose tissue (Golia et al, 2014;Xu et al, 2017;Yamada et al, 2017;da Silva et al, 2018;Pengrattanachot et al, 2020), it has been reported that statins can induce insulin resistance via activation of caspase-1/IL-1β inflammasomes in adipose tissue (Henriksbo et al, 2019) and Ator could trigger liver toxicity in diabetic rats by promoting the generation of inflammation (Zeng and Liu, 2019). Moreover, we did not find that Ator could directly alter the NF-κB signaling pathway in Caco 2 cells.…”
Section: Discussionmentioning
confidence: 99%
“…The transcriptome of pancreatic islets from mice with similar Ator treatment has also shown activated NF-κB signaling and enhanced metabolic inflammation (Shen et al, 2020). Though the anti-inflammatory effects of statins have been reported in traumatic brain injury, HFD-induced renal injury, endothelial dysfunction, and cardiac and adipose tissue (Golia et al, 2014;Xu et al, 2017;Yamada et al, 2017;da Silva et al, 2018;Pengrattanachot et al, 2020), it has been reported that statins can induce insulin resistance via activation of caspase-1/IL-1β inflammasomes in adipose tissue (Henriksbo et al, 2019) and Ator could trigger liver toxicity in diabetic rats by promoting the generation of inflammation (Zeng and Liu, 2019). Moreover, we did not find that Ator could directly alter the NF-κB signaling pathway in Caco 2 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Therapeutic and biological properties of ATV at low doses are anti-inflammatory (10 mg/kg for 10 days), 9 antioxidant (0.1 and 1 mg/kg for 6 weeks), 10 and anti-apoptotic 9 properties. Complications of high doses of atorvastatin have been reported in some organs, such as, the liver (20 mg/kg for 10 days), 11 kidney (150 mg/ kg/day for 7 days), 12 and testis. 13 But, Lori et al stated atorvastatin at low doses have no side effects on fertility and reproduction in male and female rats.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the hepatocyte injury results in complex biological events that include neutrophil infiltration and activation of Kupffer cells. Such response stimulates apoptotic pathways and the release of inflammatory cytokines [ 8 ].…”
Section: Introductionmentioning
confidence: 99%